FC 100ASSOCIATION OF SINGLE AND SERIAL MEASURES OF SERUM PHOSPHORUS WITH ADVERSE OUTCOMES IN PATIENTS ON PERITONEAL DIALYSIS: RESULTS FROM THE INTERNATIONAL PDOPPS. (29th May 2021) - Lopes, Marcelo; Karaboyas, Angelo; Johnson, David W; Kanjanabuch, Talerngsak; Wilkie, Martin; Nitta, Kosaku; Kawanishi, Hideki; Foote, Bryce S; Pisoni, Ronald
Abstract: Background and Aims: While it has been established that high serum phosphorus is associated with mortality in hemodialysis (HD) patients, there is limited evidence in the peritoneal dialysis (PD) setting. We evaluated the association of serum phosphorus with mortality and major adverse cardiovascular events (MACE) in patients on PD, and investigated various parameterizations using single and serial measurements of serum phosphorus. Method: We utilized data from 7 countries in phase 1 (2014-2017) of the Peritoneal Dialysis Outcomes and Practice Patterns Study (PDOPPS): Australia, Canada, Japan, New Zealand, Thailand, the UK, and the US. We investigated the association of serum phosphorus and 3 outcomes: all-cause mortality, cardiovascular (CV) mortality, and MACE (CV mortality + non-fatal angina, myocardial infarction, stroke, and heart failure). We parameterized serum phosphorus using 4 different methods: (1) single measurement of baseline serum phosphorus [most recent measurement during 6-month run-in period]; (2) mean serum phosphorus over a 6-month run-in period; (3) number of months (over the past 6 months) with serum phosphorus above the target range (>4.5 mg/dL); (4) mean area-under-the-curve (AUC), calculated as the average amount of time spent with serum phosphorus >4.5 mg/dL multiplied by the extent to which this threshold was exceeded over 6 months. Cox regression was used to estimate the association between each of these 4 exposures with the time-to-event outcomes, in models thoroughly adjusted for possible confounders. Follow-up began after the 6-month run-in period and continued until the outcome occurred, 7 days after leaving the facility due to transfer or change in kidney replacement therapy modality, loss to follow-up, or end of study phase (whichever event occurred first). Results: Our sample consisted of 5904 patients who were on PD. Those with higher serum phosphorus levels were younger and had lower hemoglobin levels. Compared to patients with serum phosphorus ≥3.5 to <4.5 mg/dL, we found an all-cause mortality hazard ratio (HR) of 1.62 (95% CI: 1.19, 2.20) for patients with serum phosphorus ≥ 7 mg/dL. Strong associations were also observed using serial phosphorus measures [Table]. For example, compared to the reference group of AUC=0, the HR (95% CI) of death was 1.49 (1.10, 2.00) for AUC >1 to 2; and 1.67 (1.15, 2.41) for AUC >2. Akaike Information Criteria (AIC) results showed that, among the 4 exposures, AUC was the strongest predictor of all-cause mortality, and the single phosphorus measure was the weakest predictor. Associations between serum phosphorus and adverse outcomes were generally stronger for CV death and MACE than for all-cause mortality [Table]. Conclusion: As seen in HD patients, this analysis demonstrates that serum phosphorus is a strong predictor of adverse outcomes in patients on PD. When considering serial measurements of serum phosphorus, rates of adverse events began to rise at phosphorus levels >4.5 mg/dL. As recommended by KDIGO guidelines, serial measurements that consider a history of serum phosphorus excursions >4.5 mg/dL should be considered when assessing risks of adverse outcomes.